ANALISIS MANAJEMEN PRIVASI KOMUNIKASI KORBAN CYBERSTALKING DALAM FACEBOOK - Putri, Dian Kartika; Nirwana, Maya Diah; Sobari, Wawan (Jurnal Interaktif, 2010)
The Internet grows broader from search engines to social networking sites like Facebook. Facebook offered facilities and new function (for examples: sosial network, micro blogging, messenger, image sharing, social bookmarking, blogging, video sharing, and Internet marketing)Â  that lucrative to their users where the users could make friends, chat, and even discuss. Facebook likes a real life is not free from crime or even cybercrime. There are many kinds of cybercrime on Facebook, one of them is cyberstalking (a course of conduct directed at a specific person that would cause a reasonable person to feel fear). Now, there are many cases of complaint that included authorities by certain people consequence of slander, kidnapping, fraud, defamation through Facebook. Thus, researcher wanted to know about cause of development of these cases. The purpose of this research was to find out why being the victims of cyberstalking and how communication privacy management done by the victims. This research also wants to find out the media literacy and media diet, along with how prevention and precaution for cyberstalking victims on Facebook. The approach of this research was qualitative with case study method using pattern of pairing techniques. Data collection techniques used in this research are Internet Ethnography, participant observation, interviews, media uses diaries, documentation, and archive recordings.The results from this research was cyberstalking victims on Facebook did not fully applied communication privacy management. In addition, media literacy has not applied to Facebook by them. The researchers interested to create a model of Facebook Literacy as prevention and precaution for cyberstalking victims. Facebook Literacy is a model which includes techniques and ways to use Facebook securely to prevent cyberstalking.Key words: Communication Privacy Management; Facebook; Cyberstalking